Nicaraguakanalens införande och dess påverkan på containertrafiken - Ramström, Kerstin; Stuchly, Selma (My University, 2016)
Global trade requires goods to be transported around the world where shipping plays a major role. The introduction and development of the containerized segment has led to efficient and safe transportation of goods throughout the whole supply chain. Small margins and a competitive environment have become characteristics for the industry. This put a lot of pressure on the shipping companies to be cost efficient in order to be profitable. Increasing the vessel’s size has therefore become a trend within the industry in order to benefit from economies of scale. The main question of this report is how the planned canal through Nicaragua might affect the container vessels’ trade routes. The Nicaragua Canal is planned to handle vessels with a capacity of up to 25 000 TEU. With its position in Central America, it is a close option to the existing canal in Panama, which at the moment can handle vessels with a capacity of up to 5 000 TEU. The thesis is based on interviews with shipping companies in order to identify which factors that form the basis of a decision regarding the transport route and thus the choice of canal. An interview was made with the Panama Canal Authority in order to get their view of the competition, and how it could affect the flow of goods through the Panama Canal. A simplified calculation has been made in order to see what the difference in distance, and thus time, could be on the main trade route between Asia and US east coast when using the Nicaragua Canal compared to the Panama Canal. Furthermore, the report is based on literature studies and information gathered from various articles. The authors have concluded that the decision regarding trade route and its possible options will always come down to the total cost for the shipping company. It is therefore likely that the shipping companies that handle trade routes where there is a big flow of goods will use the Nicaragua Canal before the Panama Canal in order to benefit from economies of scale. A prerequisite for this is that the total cost does not increase; this is why all costs involved have to be taken into consideration. It is therefore also likely that smaller shipping companies, without the intention to increase their vessel’s size, may use the Nicaragua Canal, provided that it would mean a lower cost for the company in total.
Keywords: Transport; Transportteknik och logistik; Transport; Transport Systems and Logistics